2021
DOI: 10.3390/jcm10112230
|View full text |Cite
|
Sign up to set email alerts
|

Locked Away—Prophylaxis and Management of Catheter Related Thrombosis in Hemodialysis

Abstract: Reliable vascular access is necessary for effective hemodialysis. Guidelines recommend chronic hemodialysis via an arteriovenous fistula (AVF), however, in a significant number of patients, permanent central venous catheters (CVCs) are used. The use of a tunneled catheter is acceptable if the estimated dialysis time is less than a year or it is not possible to create an AVF. The main complications associated with CVC include thrombosis and catheter-related bloodstream infections (CRBSIs), which may result in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
1
1
0
1
Order By: Relevance
“…Five (total of 65 patients) found no AEs [15,19e22], while four studies (450 patients) observed 45 patients (10%) with drug-related AEs [12e14,23], mainly pain, taste changes, dyspnea and nausea, vomiting or anorexia. These symptoms corroborate the findings of our study and those reported in oncology and dialysis patients [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…Five (total of 65 patients) found no AEs [15,19e22], while four studies (450 patients) observed 45 patients (10%) with drug-related AEs [12e14,23], mainly pain, taste changes, dyspnea and nausea, vomiting or anorexia. These symptoms corroborate the findings of our study and those reported in oncology and dialysis patients [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…Las directrices recomiendan la HD crónica a través de una FAV; sin embargo, en un número importante de pacientes se utilizan CVC permanentes. El uso de un catéter tunelizado es aceptable si el tiempo estimado de HD es inferior a un año o no es posible crear una FAV (33,34) . Como siempre lo mencionan los diferentes estudios referenciados, las complicaciones más comunes del CVC para HD son las infecciones del torrente sanguíneo relacionadas con el CVC de ahí la importancia en determinar las variables y la prevalencia de las infecciones (35) .…”
Section: Discussionunclassified
“…Placing central venous catheter, hemodialysis catheter and radial artery catheter, long-term intravenous uid infusion, central venous pressure and arterial monitoring, hemodialysis and ECMO are important treatment methods in emergency and critical care departments (1)(2)(3). However, catheter-related infections and thrombosis are common and serious complications after implantation (4), and effective anticoagulation is usually needed in clinical practice to prevent and treat problems such as thrombosis (5)(6)(7)(8)(9). But once a catheter infection occurs, it is necessary to remove the catheter, conduct catheter end and blood culture to determine the source of infection and bacterial species, use effective antibiotics, and reinsert the catheter in another location.…”
Section: Introductionmentioning
confidence: 99%